Design and implementation of model predictive control for microgrid energy system with power quality improvement features. Issue 12 (2nd December 2021) - Akhtar, Iram; kirmani, Sheeraz
ABSTRACT: The harmful outcome of fossil fuel emission and growing concern about the deficiency of power resources has started a new requirement of cleaner, reliable, and sustainable energy resources. Thus, wind power and solar energy based systems are the best emerging energy sources amongst the various renewable energy resources. The proposed system involves a boost converter with an inverter circuit, where first solar and wind energy is regulated, and the inverter is employed for grid integration. In the proposed work, model predictive control is applied to a 3-phase inverter and it uses a model to estimate the predictions of upcoming values of the system voltage for a provided sequence of voltages. Further, the cosine firing angle arrangement is also used for adjusting the output voltage of the boost converter. The three-phase inverter is also employed as a harmonic reduction device, this allows the utility grid to continuously supply or absorb the good quality of power. The proposed approach escapes the use of nonlinear and linear controllers and it does not include the modulator, hence this is a simple method and the control algorithm is easy to implement. The outcomes show that the planned scheme has excellent performance.